Comparison of the efficacy of a dentifrice containing 1.5% arginine and 1450 ppm fluoride to a dentifrice containing 1450 ppm fluoride alone in the management of early coronal caries as assessed using Quantitative Light-induced Fluorescence - Srisilapanan P. (2014)
Objective: To compare the efficacy of a new dentifrice containing 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride to a matched, positive control dentifrice containing 1450 ppm fluoride in arresting and reversing early coronal caries lesions in children using Quantitative Light-induced Fluorescence (QLF). Study design: 331 children from Chiang Mai, Thailand, aged 7-14 years, with one or more visible early enamel caries lesions on the upper anterior teeth, completed the study. The new dentifrice contained 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride, as sodium monofluorophosphate; the matched positive control contained 1450 ppm fluoride only. Subjects brushed twice daily at home and additionally once on school days under teacher's supervision. Digital images of the upper six anterior teeth were captured at the baseline, 3- and 6-month examinations using a custom apparatus for reproducible acquisition of Quantitative Light-induced Fluorescence data. Results: At the 3-month examination, the ΔQ (representing lesion volume) for the test group decreased from a mean of 28.62 at baseline to 20.53 mm 2% and for the positive control group to 23.38 mm2%. The difference between groups was not statistically significant (p = 0.055). At the 6-month examination, the ΔQ decreased for the test group to 15.85 mm 2% and for the positive control group to 20.35 mm2%. The difference between groups was statistically significant (p < 0.001). Conclusion: A new dentifrice containing 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride, as sodium monofluorophosphate, provided statistically significant superior efficacy in arresting and reversing active coronal caries lesions in children than brushing with a matched positive control dentifrice containing fluoride alone. © 2013 Elsevier Ltd.